Determinasi Audit Report Lag - Dwi Anjani; Sigit Hermawan; Sarwenda Biduri (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
This research aims to verify and provide empirical evidences about: The effect of Auditor Switching, Going Concern Opinion, Profit or Loss of current year and Company Size to the Audit Report Lag at companies LQ-45 that are listed on Indonesian Stock Exchange during the period 2011-2015.The population of this research are the LQ-45 companies listed in Indonesia Stock Exchange during the period 2011-2015. Sampling method using purposive sampling and obtain 15 companies. Data collection method used is the documentation. The analysis used is multiple linear regression analysis to test the hypothesis. The results shows that Auditor Switching and Opini Going Concern does not effect to Audit Report Lag partially, but Profit or Loss of current year and Company Size gave negative effect on Audit Report Lag partially. Auditor Switching, Opini Going Concern, Profit or Loss in year going and Company Size gave significant effect on Audit Report Lag simultaneously.